ANALISIS PERTANGGUNGJAWABAN KORPORASI DALAM TINDAK PIDANA LINGKUNGAN HIDUP: STUDI KASUS PUTUSAN NOMOR 206/PID.B/LH/2022/PN BTG - Pravangastha, Kanez; Zulfiani, Anita (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
This research aims to find out whether a corporation is the subject of a criminal act, which is a legal entity or business that has its own identity, its own wealth is separate from the wealth of its members, and the essence of this research is what form of corporate responsibility takes in environmental crimes based on decision no. 206/Pid.B/LH/2022/PN Btg. This research uses normative legal research methods. The results of this research show that the corporation was sentenced to a criminal sentence in the Batang District Court's decision, and the criminal elements have been met according to the provisions stipulated in the relevant law